Treatment of an anterior open bite, bimaxillary protrusion and mesiocclusion by the extraction of premolars and the use of clear aligners - Xiang Xiaosong; Wang Chunlin; Guan Xiaohang; Wang Lu; Cang Song (Sciendo, 2023)
An anterior open bite may be orthodontically treated by either the intrusion of posterior teeth, the extrusion of anterior teeth, or a combination of both. An improvement in bimaxillary protrusion often involves the extraction of premolars and the retraction of the anterior teeth. The treatment of mesiocclusion mainly involves the mesial and/or distal movement of the molars. However, these three types of malocclusions pose significant treatment challenges when using clear aligners. The present case report describes the treatment of a 24-year-old female patient who presented with the above characteristics, which affected her confidence, willingness to smile and masticatory function. A four-premolar extraction plan was designed to resolve the problems using clear aligners as the patient rejected fixed or visible appliances. After 33 months of orthodontic therapy, except for the counter-clockwise rotation of the mandible and the decrease of facial height, the other objectives established in the pre-treatment plan were achieved, and the patient was satisfied with the results. The combination of clear aligners and premolar extractions effectively corrected the skeletal anterior open bite, bimaxillary dentoalveolar protrusion, and mesiocclusion.